Tribological properties of bronze surface with dimple textures fabricated by the indentation method. (October 2020) - Wu, Jianzhao; Yu, Aibing; Chen, Qiujie; Wu, Maochao; Sun, Lei; Yuan, Jiandong
Surface texturing is an effective approach to improve the tribological properties of mechanical components. An indentation method is presented to fabricate dimple textures on bronze specimen surfaces. Graphite was selected as the mating balls in ball-on-disc wear tests. The worn surfaces and the indented dimples heaped with the thin ribbon debris were observed by microscope. The morphology and evolution of wear debris were employed to explain the influence of indented dimple textures. The experimental results indicate that the generation of thin ribbon debris is due to the edge hardening of indented dimple. The thin ribbon debris and the indented conical dimple are conducive to the debris heaping on slopes of dimples, which can facilitate the formation of the graphite-rich transfer layers on indented dimple surface. Compared with nontextured surface, indented dimple surface has lower coefficients of friction and slighter wear. The tribological properties of indented dimple surface are improved because of the edge hardening, the debris heaping and the formation of transfer layers.